Digital microclimate simulation models to support innovative management and preventive conservation processes in cultural sites - Marco Pretelli; Leila Signorelli; Maria Antonietta De Vivo (Vitruvio: International Journal of Architectural Technology and Sustainability)
Among the least investigated aspects in historical architecture, one is the microclimatic behaviour linked to the preventive conservation of cultural heritage. This aspect should be studied intensively since it is closely related to any deterioration phenomenon of materials and can have a crucial role in updating management systems of cultural sites. Today the sensors that monitor environmental parameters can transfer data in real time into a continuous monitoring logic (cloud platforms) and this, in addition to the development of software capable of modelling the thermo-hygrometric behaviour of buildings, opens up new lines of research. The authors believe that it represents one of the most promising areas of investigation and capable of offering greater results in terms of preventive and planned measures. This contribution collects an experience recently conducted, financed by the Ministry of University and Research, in one of the most prestigious Italian museums, the National Archaeological Museum of Naples (MANN). The monitoring and modelling methodologies are illustrated, as well as the objectives of the intervention, with a view to a fruition that holds the psycho-physical well-being of staff and visitors and the conservation of heritage as close as possible. The results are closely linked to the pandemic experience, with the secondary objective of risk prevention for people and cultural heritage.